Rates of Transformation of Methyl Parathion and Diethyl Phthalate by Aufwuchs Microorganisms - Lewis, David L. (1981)
Using batch cultures, we determined transformation rates for low concentrations of two toxicants—an insecticide, methyl parathion (O,O-dimethyl O-p-nitrophenyl phosphorothioate), and a plasticizer, diethyl phthalate—by aufwuchs, aquatic microbial growth attached to submerged surfaces or suspended in streamers or mats. Aufwuchs samples were collected from field sites, an indoor channel, and a continuous-flow fermentor. Aufwuchs fungi, protozoa, and algae did not transform methyl parathion or diethyl phthalate, but bacteria rapidly transformed both chemicals. Second-order transformation rate coefficients, K(b), based on total plate counts of bacteria in aufwuchs, were determined for potential use in a mathematical model capable of predicting the transport and fate of chemicals in aquatic systems. K(b) for both methyl parathion and diethyl phthalate decreased as the concentration of total bacteria, [B], increased in aufwuchs. This effect resulted from the proportion of nontransformer to transformer bacteria increasing as [B] increased and from the rate of transformation per transformer cell decreasing as [B] increased. First-order transformation rate coefficients, K(1), were relatively stable per unit of surface area colonized by aufwuchs, because K(b) decreased as [B] increased (K(1) = K(b) × [B]).